A Study on Factors Influencing Brand Loyalty in Mobile Service Providers Among College of Business Students of Universiti Utara Malaysia - Reena, Mohamad Nasir (2012)
Mobile phones have become a necessity in human life. This is due to technological advances that allow people to communicate with each other anywhere and at any time. This also contributes to the increase in the telecommunication sector of the country. Leading telecommunication companies are now competing with each other to become a major provider and attract more customers. This situation also will lead the customers often switch from one provider to another provider to get the best service. As competition is increasing among the companies, it is necessary for them to know about the customers’ perception on price, service quality, promotions, and trends that play a vital role in choosing the mobile service providers. This study aims to find out what are critical factors that play an important role to select the telecommunication service provider. This study was conducted among College of Business students of Universiti Utara Malaysia. The data is processed by using quantititave analysis. The method used in analyzed the data are Descriptive Analysis and Multiple Regression Analysis as there are four variables involved in this study, which are price, service quality, promotions, and trends. The results provides a comprehensive analysis of the important factors for the customer to select the mobile service providers. The analysis confirms that the significant positive relationship of trends towards brand loyalty. It will be a great challenge for the service providers to prepare their strategic plan in maintaining customer loyalty, and at the same time expending their customer base. In conclusion, the mobile service providers should emphasize the factor such as trends that can maintain customer loyalty as customers today are more intelligent and smart.